Ketahanan pangan rumah tangga peternak domba di Kecamatan Pamulihan Kabupaten Sumedang Jawa Barat - Sekarizky; Cecep Firmansyah; Sondi Kuswaryan (Fakultas Pertanian Universitas Majalengka, 2025)
Sheep farming was one of the primary sources of household income, playing a crucial role in sustaining the livelihoods of farming households, particularly in rural areas. This study aimed to analyze the level of food security among sheep-farming households and determine the contribution of sheep farming to meeting household food needs. The research was conducted in Pamulihan Subdistrict, Sumedang Regency, with a total of 91 households selected proportionally from five villages. The method employed was a survey conducted through structured interviews and energy consumption measurement using the 3-day, 24-hour food recall method. The results showed that the average annual income from sheep farming was IDR 4,144,716.90 per business unit, equivalent to IDR 342,642.90 per month, comprising food expenditure of IDR 1,665,977.98 per month and non-food expenditure of IDR 1,251,089.59 per month. The average household energy consumption was recorded at 5.929.78 kcal/household/day (89.95% of the Recommended Dietary Allowance), and protein consumption was 164.67 grams/household/day (86.81% of the Recommended Dietary Allowance), with the share of food expenditure reaching 57.11%. The distribution of household food security status included 35.16% food-secure, 18.68% food-insecure, 26.37% food-vulnerable, and 19.78% food-secure. Sheep farming served as an additional source of income as well as a form of savings that could be liquidated when needed, particularly in urgent financial situations, to access food. However, its contribution to food expenditure only reached 23,47%. Therefore, it was important to increase household income through income diversification and to promote the development of sheep farming as a strategy to improve welfare and food security in rural areas.